PENERAPAN MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MEDIA WORDWALL PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS III SD NEGERI 1 TERUSAN - Intan Safitri, Ayu; Nur Fitriyana; Tio Gusti Satria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the completeness of Pancasila Education learning outcomes of third-grade students at SD Negeri 1 Terusan after the implementation of the Talking Stick learning model assisted by Wordwall media. The background of this study is the low completeness of student learning outcomes, as learning has largely been dominated by the lecture method and has not utilized interactive digital media. This study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The research sample was determined using a simple random sampling technique, resulting in 22 students from class III A. Data were collected through a multiple-choice test consisting of 12 valid and reliable items. Data were analyzed using the chi-square normality test and the t-test hypothesis test. The results showed that the average pretest score of 60.36 with a completeness percentage of 31.82% increased to 83.68 with a completeness percentage of 86.36% on the posttest, an increase of 38.64%. The hypothesis test results showed a calculated t-value of 5.191, greater than the t-table value of 1.721 at a significance level of 0.05, so H0 was rejected and Ha was accepted. It can therefore be concluded that the implementation of the Talking Stick learning model assisted by Wordwall media significantly improved the completeness of Pancasila Education learning outcomes among third-grade students at SD Negeri 1 Terusan.